Obtaining phycobiliprotein-Obtaining phycobiliprotein-containing Nostoc linckia (Roth.) Born. et Flah biomass via bioconversation of waste water from reticulating aquaculture systems (RAS)containing Nostoc linckia (Roth.) Born. et Flah biomass via bioconversation of waste water from reticulating aquaculture systems (RAS) - Чебан, Лариса (My University, 2020)
The paper studies the possibility of bioconversion of waste water from recirculating aquaculture systems (RAS). For this purpose, cyanobacteria Nostoc linckia (Roth.) Born. et Flah. was grown on waste water from RAS. In the process of cultivation, indicators of total mineralization, pH, and culture density were monitored. In the waste water, the content of various forms of nitrogen (NH4+, NO3-, NO2-), the content of P and S before and after the growth of cyanobacteria were determined It was noted that as a result of growing N. linckia in RAS waste water, a decrease in the content of various forms of nitrogen, sulfur and phosphorus is observed. Also, the content of phosphates decreased from 35×10-3 to 5×10-3 mg.L-1 and the content of sulfates from 95×10-3 to 25×10-3 mg.L-1. Moreover, the resulting biomass of cyanobacteria contained 57 % of proteins, 20 % of lipids and 11% of carbohydrates. It was found that N. linckia biomass is a promising source of phycobiliprotein pigments: phycocyanin, allophycocyanin and phycoerythrin.
Keywords: Bioconversion; Nostoc linckia; Phycobiliprotein pigments; Recirculating aquaculture systems; Waste water